2013
DOI: 10.1055/s-0033-1355599
|View full text |Cite
|
Sign up to set email alerts
|

Die Diagnose des Phäochromozytoms und Paraganglioms

Abstract: Zusammenfassung Hintergrund: Stark erh?hte Plasma-Metanephrinkonzentrationen weisen auf ein Ph?ochromozytom/Paragangliom (P/PGL) hin. Im Gegensatz dazu besteht bei leicht erh?hten Werten erhebliche diagnostische Unsicherheit. In der vorliegenden Arbeit wurde untersucht, ob der Clonidin-Suppressionstest (CST) in diesen F?llen zum Tumornachweis oder -ausschluss beitragen kann. Patienten und Methoden: 24 Patienten mit grenzwertiger Erh?hung der freien Metanephrine und/oder Katecholamine im Plasma wurden in die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…Applying these cutoffs, the diagnostic sensitivity and specificity were as high as 96% and 100%. Similar results were reported in a second study, 16 and these thresholds are currently recommended by an international guideline. 2 One of these studies included 97 patients (48 with and 49 without PPGL), but a high proportion of the PPGL patients had markedly elevated screening NMN (in whom the diagnosis of PPGL could have been established without CST).…”
Section: Remde Et Alsupporting
confidence: 89%
See 2 more Smart Citations
“…Applying these cutoffs, the diagnostic sensitivity and specificity were as high as 96% and 100%. Similar results were reported in a second study, 16 and these thresholds are currently recommended by an international guideline. 2 One of these studies included 97 patients (48 with and 49 without PPGL), but a high proportion of the PPGL patients had markedly elevated screening NMN (in whom the diagnosis of PPGL could have been established without CST).…”
Section: Remde Et Alsupporting
confidence: 89%
“…Our study revealed another interesting aspect. The normalization of plasma NMN at baseline sampling of the CST in more than half of the patients, which has also been observed in a smaller study, 16 suggests that repeated measurement of plasma MN and NMN with optimized preanalytics would be sufficient to exclude PPGL in a large proportion of patients. However, due to practical issues (eg, long distance to the specialized center, delayed availability of laboratory results), it can be reasonable to proceed occasionally directly to a CST.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In other patients with smaller increases of single metabolites, posttest probability must consider pretest risk. In such cases, the clonidine suppression test can be helpful to differentiate false-positive from true-positive test results [45,50].…”
Section: Personalized Interpretation Of Test Resultsmentioning
confidence: 99%
“…Of note, immunoassays often underestimate plasma metanephrines, negatively impacting diagnostic performance [44]. An activated sympathetic nervous system during biochemical testing is associated with high rates of false-positive results and compromised diagnostic accuracy [45][46][47]. Sampling blood for plasma measurements in particular should therefore be carried out under stress-free conditions in the supine position (Supplemental file §1, http://links.lww.com/HJH/B310).…”
Section: What Is the Preferred Initial Biochemical Test?mentioning
confidence: 99%